Deep Brain Stimulation of the Forel’s Field for Dystonia: Preliminary Results - Horisawa, Shiro; Kohara, Kotaro; Murakami, Masato; Fukui, Atsushi; Kawamata, Takakazu; Taira, Takaomi (Frontiers in Human Neuroscience, 2021)
The field of Forel (FF) is a subthalamic area through which the pallidothalamic tracts originating from the globus pallidus internus (GPi) traverse. The FF was used as a stereotactic surgical target (ablation and stimulation) to treat cervical dystonia in the 1960s and 1970s. Although recent studies have reappraised the ablation and stimulation of the pallidothalamic tract at FF for Parkinson’s disease, the efficacy of deep brain stimulation of FF (FF-DBS) for dystonia has not been well investigated. To confirm the efficacy and stimulation-induced adverse effects of FF-DBS, three consecutive patients with medically refractory dystonia who underwent FF-DBS were analyzed (tongue protrusion dystonia, cranio-cervico-axial dystonia, hemidystonia). Compared to the Burke‐Fahn‐Marsden Dystonia Rating Scale Movement scale scores before surgery (23.3 ± 12.7), improvements were observed at 1 week (8.3 ± 5.9), 3 months (5.3 ± 5.9), and 6 months (4.7 ± 4.7, p=0.0282) after surgery. Two patients had stimulation-induced complications, including bradykinesia and postural instability, all well controlled by stimulation adjustments.